Pengaruh Lingkungan Internal Sekolah Terhadap Pemahaman Agama dan Nilai Moral Siswa di SMK Ma’arif 1 Kebumen - Mauly, Sahrul; Mahfudz, Ali (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
This study aims to determine and analyze the influence of the internal school environment on students' understanding of religion and moral values ​​at SMK Ma'arif 1 Kebumen and identify factors within the internal school environment that influence students' understanding of religion and moral values ​​at SMK Ma'arif 1 Kebumen. This study is motivated by the importance of the internal school environment in shaping students' understanding of religion and moral values. This study is a qualitative study with a descriptive approach. The internal school environment studied includes aspects such as the school's religious culture, teacher role models, routine religious activities, and interaction patterns between students, teachers, and educational staff. The research method used is descriptive qualitative with a field study approach. Informants consisted of the principal, vice principal, student staff, Islamic religious education teachers, Guidance and Counseling (BK) teachers, students, and residents around SMK Ma'arif 1 Kebumen. Data collection techniques include observation, interviews, and documentation, with data analysis using the Miles and Huberman model (data reduction, data presentation, and conclusion drawing). Research results show that the internal school environment has a significant influence on shaping and strengthening students' religious understanding and moral values. Teachers' exemplary behavior in daily behavior, the organization of religious activities such as congregational prayer, religious study, and the practice of polite behavior within the school environment have been shown to play a significant role in instilling religious and moral values ​​in students. By creating a religious and conducive school environment, students more easily internalize spiritual and ethical values ​​in their daily lives, both inside and outside of school. The internal school environment serves not only as a place for academic learning but also as an effective means of character education based on religious and moral values.